2004
DOI: 10.1890/03-0029
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Dynamics of Alternative Reproductive Strategies: The Role of Neighbors

Abstract: In territorial species, the reproductive success of a male is dependent on the quality of his territory. One important component of territory quality is spatial location. High‐quality territories not only should be located in areas of high food abundance and low predation, but also should be located in areas that offer optimal amounts of social interaction. Such optima might be different for individuals according to their sex, dominance, or genotype. We studied territory quality (size, vegetation structure, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 42 publications
(62 reference statements)
1
65
0
1
Order By: Relevance
“…For instance, there is evidence that conspecific attraction of the Least Flycatcher (Empidonax minimus) could be driven by a hidden-lek strategy (Wagner et al 1996, Tarof et al 2005, Fletcher 2007). However, not all individuals may benefit from increased paternity by settling close to conspecifics, and some males (e.g., subdominant males) might benefit from avoiding settling close to dominant males (Greene et al 2000, Formica et al 2004.…”
Section: Ultimate Factors In Conspecific Attractionmentioning
confidence: 99%
“…For instance, there is evidence that conspecific attraction of the Least Flycatcher (Empidonax minimus) could be driven by a hidden-lek strategy (Wagner et al 1996, Tarof et al 2005, Fletcher 2007). However, not all individuals may benefit from increased paternity by settling close to conspecifics, and some males (e.g., subdominant males) might benefit from avoiding settling close to dominant males (Greene et al 2000, Formica et al 2004.…”
Section: Ultimate Factors In Conspecific Attractionmentioning
confidence: 99%
“…In particular, quality estimates can aVect Wtness in Wve ways, which can be considered as working hypotheses: (b1) territory quality is the only determinant of Wtness (Alatalo et al 1986;Warner 1987;Pärt 2001;Przybylo et al 2001); (b2) individual quality is the only determinant of Wtness (Simmons 1988;Horn et al 1993;Carrete et al 2006); (b3) both individual and territory quality independently aVect Wtness (Hill 1988;Bart and Earnst 1999); (b4) individual and territory quality aVect Wtness but their eVect is interactive (Lõh-mus and Vali 2004); and (b5) Wtness is related to neither individual nor territory quality (Leonard and Picman 1988;Formica et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Behavioural studies over the next two decades demonstrated that TS and WS birds often differ in territorial aggression, parenting behaviour and mating strategy (Collins & Houtman, 1999; Formica & Tuttle, 2009; Knapton & Falls, 1984; Kopachena & Falls, 1993a, 1993a, b; Tuttle, 1993, 2003), which led to a consensus in the current literature that morphs show alternative reproductive strategies (Formica et al, 2004; Formica & Tuttle, 2009; Maney, 2008; Tuttle, 2003). Multiple authors have since described a number of endocrine differences between the morphs (Lake et al, 2008; Maney, 2008; Horton & Holberton, 2009, 2010; Spinney et al, 2006; Swett & Breuner, 2008, 2009), suggesting that morph-typic strategies may be hormone mediated.…”
mentioning
confidence: 99%